Changes in the chemical and sensory properties of green mango juice during storage - Francisco, Ma. Leonora dL (2001)
A ready to drink mango green juice was formulated and the effect of the storage temperature on the chemical qualities of green mango juice was determined. Formulation and process development of the product include pasteurization at 85%C, packaging of juice in tin cans, use of acesulfame-K and aspartame as sweeteners, and addition of Vitamin C at level of 102 mg/250 mL serving. Only 24% of the added Vitamin C was retained after the green mango juice reached 85C. Storage of green mango juice at three different temperatures resulted to significant changes in sensory properties and Vitamin C content. Chemical and sensory properties did not correlate well with each other because of the insignificant changes obtained. regression analysis for chemical properties as a function of time and temperature showed that the change in Vitamin C content of the green mango juice stored at three different temperatures were significant at 5% level. Both plots of Vitamin C and log of Vitamin C vs. time showed goodness of fit for a zero order and first order reaction, respectively. However, higher correlations were obtained for values fitted in zero order reaction. reaction rate constants obtained from the slope of Vitamin C vs. time increased as storage temperature increased.